Deformation analysis on F138 austenitic stainless steel: ECAE and rolling - de Vincentis, Natalia Soledad (2014)
Twinning is an alternative mechanism to achieve ultra-fine grain structures through severe plastic deformation. The properties induced in a plastically deformed material are highly dependent on the degree of deformation, accumulated deformation energy and details on grain sizes and microstructure, which are on the scale of some tens of nanometers; therefore it is very important to understand misorientation distributions and dislocation arrays developed in the samples. In this work an F138 austenitic stainless steel was solution heat treated, deformed by Equal Channel Angular Extrusion (ECAE) at room temperature up to four passes, and rolled up to 70% thickness reduction at room temperature. The microstructure evolution was analyzed by x-ray diffraction and domain sizes calculated by Convolutional Multiple Whole Profile (CMWP) model, the misorientation boundaries were measured by electron backscattered diffraction (EBSD), and transmission electron microscopy. Mechanical behavior was tested by tensile tests.